Retroperitoneal unicentric Castleman’s disease (giant lymph node hyperplasia): case report - Waisberg, Jaques (2007)
CONTEXT AND OBJECTIVE: Castleman’s disease, or giant lymph node hyperplasia, is a rare disorder of the lymphoid tissue that causes lymph node enlargement. It is considered benign in its localized form, but aggressive in the multicentric type. The defi nitive diagnosis is based on postoperative pathological fi ndings. The aim here was to describe a case of retroperitoneal unicentric Castleman’s disease in the retroperitoneum. CASE REPORT: A 61-year-old white male with weight loss and listlessness presented with moderate arterial hypertension and leukopenia. Abdominal tomography revealed a 5 x 4 x 5 cm oval mass of low attenuation, with inner calcifi - cation and intense enhancement on intravenous contrast, located in the retroperitoneal region, between the left kidney and the aorta, at the renal hilus. Exploratory laparotomy revealed a non-pulsatile solid oval mass situated in the retroperitoneum, adjacent to the left renal hilus. The retroperitoneal lesion was removed in its entirety. Examination of frozen samples revealed benign lymph node tissue and histopathological examination of the surgical sample revealed hyaline-vascular giant lymph node hyperplasia (Castleman’s disease). The patient was discharged on the 12th day without signifi cant events. Two months after the operation, the patient was readmitted with severe cardiac insuffi ciency, acute renal failure and bronchopneumonia, which progressed to acute respiratory insuffi ciency, sepsis and death.